The Magnificent Maya - Time-Life Books (Alexandria, Va. : Time-Life Books, 1993)
Explores the history of Maya civilization through the archaeological discoveries found in Mexico and Central America.
ch. 1. Cities buried in forests, desolate, without a name -- ch. 2. Gods, blood, and kings -- ch. 3. Royalty and the seeds of doom -- ch. 4. Yucatan, where the lucky days ran out.
Includes bibliographical references (p. 163-165) and index.
Keywords: Mayas -- Antiquities; Central America -- Antiquities; Mexico -- Antiquities; Mayas; Central America